Effectiveness of Jicama Probiotic Yoghurt (Pachyrhizus erosus) on Blood Glucose in Diabetic Mice - Yuniritha, Eva; Avelia, Annisa; ., Andrafikar (KnE Life Sciences, 2019)
Background: Diabetes Mellitus (DM) is a degenerative disease population increases every year. DM was ranked sixth as the cause of death. About 1.3 million people died because of diabetes and 4% died before the age of 70 years. DM auto-oxidation causes glucose to increase reactive oxygen compounds. One of the DM management is a complementary therapy using a functional food ingredient, namely, jicama and probiotics. Probiotics and jicama contain active compounds in the form of inulin and BAL and are able to control blood glucose levels. This study aims to determine the effectiveness of jicama probiotic yogurt on blood glucose levels in diabetic mice. Methods: This research is a quasi-experimental with pre–post-test control group, using a sample of DDY strain mice according to the criteria. Samples were given treatment probiotic yogurt and jicama probiotic yogurt 2 ml for seven days in the treatment group and one group of non-treated controls. The mean obtained were analyzed by dependent t-test, independent t-test, and one-way ANOVA test. Result and Conclusion: The results showed that there was a decrease in blood glucose levels in the probiotic yogurt group amounting to 296.62 mg/dL and jicama probiotic yogurt of 337.57 mg/dL, while the control group increased by 43.57 mg/dL. Results: One way ANOVA test showed jicama probiotic yogurt more effectively decreases blood glucose levels than the probiotic yogurt (p = 0.00). Jicama probiotic yogurt can be used as an alternative complementary therapy for patients with diabetes mellitus.